Analisis Startegi Pemasaran dalam Meningkatkan Penjualan Blooming Bouquet di Kabupaten Bengkayang (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to find out marketing strategies to increase sales and develop blooming bouquet products. This research uses a descriptive method through a qualitative approach. The data collection techniques for this research are observation, interviews, and research documentation by means of interviews conducted in Bengkayang and its surroundings, there are several informants who will be interviewed, with 3 aspects of questions, the research results obtained are regarding marketing strategies in improving and developing Blooming products. bouquets use marketing strategies, there are several things that must be done by business actors, namely carrying out product innovations in terms of shapes and variants requested by consumers as well as displaying more attractive packaging.